Makna Pencobaan Berdasarkan Yakobus 1:2-8 Dan Aplikasinya Di Gereja GBI Chic’s Rawamangun - Walui, Donny Ardo Eka Dharma Putra; Walui, Berlian Purnama Sari (Sekolah Tinggi Teologi Tenggarong, 2024)
Both congregations who do not understand and some have understood the meaning of temptation, but both parties in their daily lives have not done it. The purpose of this research is how the meaning of temptation based on James 1:1-8 can be applied or practiced in everyday life, especially the congregation of GBI Chich's Rawamangun. Based on the results of this research with a literature study approach and interviews with qualitative methods, the suggestions submitted by the researcher are: First, the pastor should inform the congregation of the meaning of trials in life. Second, the pastor should give time to be able to visit the congregation's home to understand the congregation's condition and needs. Third, the pastor should provide motivation with God's word and counseling that can strengthen the congregation in facing problems. Fourth, the congregation needs fellow believers to share problems or tell about the problems they face (community). Fifth, the congregation is taught to be able to apply personal prayer, read the Bible to have sensitivity to God's will and love God more which becomes a barrier to sin. Sixth, for the College of Theology (STT) to become the backbone of the church to educate the congregation and children to provide an understanding of the meaning of temptation based on James 1: 1-8 both in the church and in the family environment.